2006
DOI: 10.1111/j.1751-1097.2006.tb09828.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethylenimine, a Cell Permeabilizer, on the Photosensitized Destruction of Algae by Methylene Blue and Nuclear Fast Red

Abstract: The present study reports the effect a cell permeabilizer, polyethylenimine (PEI) has on the photodynamic effect of methylene blue (MB) and nuclear fast red (NFR) in the presence of hydrogen peroxide (H2O2). The photosensitized destruction of the algae Chlorella vulgaris under irradiation with visible light is examined. The photodynamic effect was investigated under aerobic and anaerobic conditions. The presence of a permeabilizer during the photosensitized destruction of C. vulgaris does not enhance the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…The presence of H2O2 adds to the lifetime of singlet oxygen, and the increased lifetime of the radical species present leads to the increased destruction of C. vulgaris observed. This result is contrary to our previous work where we reported that the photosensitized destruction of the cyanobacteria S. leopolienis by a MB/H2O2 system proceeded via a Type I mechanism (43). The difference in the two species is that S. leopoliensis is a prokaryote while C. vulgaris is a eukaryote.…”
Section: Pdt Of C Vulgaris With Mb or Nfr And H2o2 Under Anaerobic Co...contrasting
confidence: 99%
“…The presence of H2O2 adds to the lifetime of singlet oxygen, and the increased lifetime of the radical species present leads to the increased destruction of C. vulgaris observed. This result is contrary to our previous work where we reported that the photosensitized destruction of the cyanobacteria S. leopolienis by a MB/H2O2 system proceeded via a Type I mechanism (43). The difference in the two species is that S. leopoliensis is a prokaryote while C. vulgaris is a eukaryote.…”
Section: Pdt Of C Vulgaris With Mb or Nfr And H2o2 Under Anaerobic Co...contrasting
confidence: 99%
“…The red-shi of the FL indicates that self-assembled aggregation of GQDs is induced by Cyt c, and the aggregation of GQDs is driven by electrostatic attraction. Cyt c is a cationic polyelectrolyte with a neutral pH 34,[44][45][46][47][48] and thus readily forms complexes with anionic GQDs. The large amount of carboxyl groups at the edge of GQDs are considered as restraining the p-p intermolecular interactions, which eventually leads to the self-assembled packing with a specic J-type aggregation induced by Cyt c. 49 The self-assembled aggregation of GQDs is further proven by transmission electron microscopy (TEM).…”
mentioning
confidence: 99%
“…We have previously reported the use of methylene blue (MB) and nuclear fast red (NFR) as biocides in the treatment of algae and cyanobacteria [24][25][26].…”
Section: Introductionmentioning
confidence: 99%